Ultrasound Improves Antimicrobial Effect of Sodium Hypochlorite and Instrumental Texture on Fresh-Cut Yellow Melon - Denes K. A. Rosario; Ana Lucia A. Duarte; Marina C. M. Madalao; Manoela C. Libardi; Luciano J. Q. Teixeira; Carlos A. Conte-Junior; Patricia C. Bernardes (Journal of Food Quality)
Ultrasound combined with sanitizers is efficient for the reduction of microbiological contaminants in fruits and vegetables. However, the physicochemical changes remain to be elucidated. Therefore, the isolated and combined effect of ultrasound (40 kHz, 500 W) and sodium hypochlorite (NaOCl) (100 mg/L) for 5 min in the bacterial microbiota and physicochemical changes on yellow melon (Cucumis melo L.) were evaluated. Mesophilic aerobic bacteria (MAB), pH, total titratable acidity (TTA), and texture profile were performed. No changes in pH and TTA (p>0.05) were obtained. Firmness, chewiness, cohesiveness, and gumminess increased (p<0.05) after the ultrasound application. A synergistic effect between ultrasound and NaOCl in the MAB reduction was achieved. Therefore, ultrasound improves the antimicrobial effect of NaOCl and texture profile without undesirable chemical changes.